2018
DOI: 10.1136/bmjopen-2017-018798
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in presenting symptoms of acute coronary syndrome: the EPIHeart cohort study

Abstract: ObjectivesPrompt diagnosis of acute coronary syndrome (ACS) remains a challenge, with presenting symptoms affecting the diagnosis algorithm and, consequently, management and outcomes. This study aimed to identify sex differences in presenting symptoms of ACS.DesignData were collected within a prospective cohort study (EPIHeart).SettingPatients with confirmed diagnosis of type 1 (primary spontaneous) ACS who were consecutively admitted to the Cardiology Department of two tertiary hospitals in Portugal between A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 40 publications
(42 reference statements)
1
30
0
Order By: Relevance
“…Women with ACS were more likely to experience higher overall symptoms distress compared to men, but the difference was not statistically significant. Araújo et al 24 found a strong relationship between female sex and pain intensity greater than 8 (range 0-10) among females less than 65 years old. Our results may have differed because our sample include females aged 21-98 years and we asked about overall symptom distress, not simply pain intensity.…”
Section: Discussionmentioning
confidence: 97%
“…Women with ACS were more likely to experience higher overall symptoms distress compared to men, but the difference was not statistically significant. Araújo et al 24 found a strong relationship between female sex and pain intensity greater than 8 (range 0-10) among females less than 65 years old. Our results may have differed because our sample include females aged 21-98 years and we asked about overall symptom distress, not simply pain intensity.…”
Section: Discussionmentioning
confidence: 97%
“…Women who present with acute and chronic cardiovascular diseases remain under-studied and, therefore, are likely under-treated (15). The clinical presentation, management, and response to therapies for MI may also be different in women compared to men (16,17). Women with NSTEMI are less likely to be treated with an early invasive strategy than men though, curiously, this did not contribute to increased mortality in women (18).…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of symptoms were stratified by age, and interaction of symptom by age was tested. Potential covariates were chosen because of reports of gender differences in prior studies 31–33 and because obesity, 17 diabetes, 34 and functional status 35 can confound the symptom experience.…”
Section: Methodsmentioning
confidence: 99%
“… 15 In contrast, women ≥65 years with ACS have been shown to experience fewer symptoms, less chest pain, and more dyspnea than younger women. 16 Many studies of symptoms of ACS focused on sex differences, 17 but few focused on how symptoms may vary between older and younger women. 16 It is important to determine (1) how symptoms experienced by older and younger women vary during an episode of potential ACS, (2) whether differences in symptoms are significant enough to warrant intervention, and (3) what interventions would be appropriate to improve clinical and patient outcomes.…”
Section: Introductionmentioning
confidence: 99%